Sumerian Mythology: A Study of Spiritual and Literary Achievement in The Third Millennium B.C. - Samuel Noah Kramer 1897-1990 (USA University of Pennsylvania, 1972)
An authoritative sketch of the great myths of the Sumerians, their myths of origins, of creation, the nether world, and the deluge.
The sources : the Sumerian literary tablets -- The scope and significance of Sumerian mythology -- Myths of Origins. The creation of the universe -- The organization of the universe. Enlil : the begetting of Nanna ; The journey of Nanna to Nippur ; Emesh and Enten : Enlil chooses the farmer-god ; The creation of the pickax ; Cattle and grain ; Enki and Ninhursag : the affairs of the watergod ; Enki and Sumer : the organization of the Earth and its cultural processes ; Enki and Eridu : the journey of the water-god to Nippur ; Inanna and Enki : the transfer of the arts of civilization from Eridu to Erech ; The creation of man -- Myths of Kur. The destruction of Kur : the slaying of the dragon ; Inanna's descent to the Nether World -- Miscellaneous myths. The deluge ; The marriage of Martu ; Inanna prefers the farmer.
Originally published: New York : Harper, 1961.
Keywords: Religions (3GdCOjGfs; General; Mythology, Sumerian